ALAM SEBAGAI SISTEM: TINJAUAN EKOLOGIS DAN ETIS DALAM PERSPEKTIF ISLAM - Abiyyah, Azhar Arij; Tauhidah, Nadhilah Amalia; Anwar, Najih (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2024)
From an Islamic perspective, humans with their role as khalifah on earth have the responsibility to care for, manage, and use their rights to nature wisely. Reported by wwf.id, that the results of the WWF Living Planet Report (LPR) 2024, the average monitored wildlife population has decreased by more than 73% in just 50 years (1970-2020). This statement is in line with that reported on nrdc.org regarding the IPCC 1.5°C special report (2018) which shows that overexploitation of natural resources contributes significantly to global climate change. This act of exploitation indicates that humans are facing a crisis of morality. This article introduces novelty by integrating scientific and ethical perspectives, aiming to create a more comprehensive framework for environmental management. This research uses a library research method with a qualitative approach. The result of this research is that all the creation of the universe in the Quran can be proven scientifically and has the order that Allah intended. Islam also teaches that human interaction with nature is functional and ethical through the principles contained, namely the principle of tawhid, the principle of trust, and the principle of Al-Hifdz Al-Mal.